2019
DOI: 10.1063/1.5121863
|View full text |Cite
|
Sign up to set email alerts
|

Structure and photophysics of indigoids for singlet fission: Cibalackrot

Abstract: We report an investigation of structure and photophysics of thin layers of cibalackrot, a sturdy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(102 citation statements)
references
References 66 publications
5
97
0
Order By: Relevance
“…The approximations make the calculations so fast that it is easily possible to search the entire 6‐dimensional space of all possible molecular pair configurations using a grid of billions of geometries, and to identify all local maxima of the SF rate. Testing at about a hundred geometries showed that the results correlated well with those obtained at a good ab initio level, both for ethylene [18] used as a model, and for cibalackrot [20] …”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…The approximations make the calculations so fast that it is easily possible to search the entire 6‐dimensional space of all possible molecular pair configurations using a grid of billions of geometries, and to identify all local maxima of the SF rate. Testing at about a hundred geometries showed that the results correlated well with those obtained at a good ab initio level, both for ethylene [18] used as a model, and for cibalackrot [20] …”
Section: Introductionsupporting
confidence: 57%
“…Still, regardless of the method of preparation and the solid chosen, But‐ 1 , Hex‐ 1 , or Ada‐ 1 , the spectra of the solids resemble the solution spectra sufficiently to instill confidence that similar assignments apply in the three cases, and that they can be discussed together. Although the dominant transitions from S 0 and T 1 do not have parallel polarizations, they do not require corrections for the effects of molecular orientation [20] when they are used for quantitation of the relative abundancies of these two states, because the samples show nearly isotropic absorbance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38,39 Now, what are the explicit scopes of T 1 -state Bairdaromaticity for the design of singlet fission chromophores, and what are the limitations? It was argued by Ryerson et al, 40 when analyzing the INDT compounds by Fallon et al, 37 that the intermediate triplet-state aromaticity yielding the E(S 1 ) = 2E(T 1 ) situation needs to be found through inspection of calculated adiabatic excitation energies. Thus, a qualitative tool should be desirable.…”
Section: ■ Introductionmentioning
confidence: 99%